On Dual Cone Theory for Euclidean Bosonic Equations - Prado-Castillo, H (Birkhauser, 2024)
In this paper we get the existence of nodal solutions and we will study some bifurcation properties for the following class of nonlocal problems (Formula presented.) where N≥3, c>0, g:RN×R→R is a C1-function, Δ is the euclidean Laplacian and the linear operator e-cΔ is defined by the Fourier transform on a certain Hilbert space. This class of problems arises as models in the mathematical physics literature. © The Author(s), under exclusive licence to Springer Nature Switzerland AG 2024.